High-thermal-conductivity and high-strength epoxy resin material as well as preparation method and application thereof
By adding specific thermal conductivity fillers and coupling agents to the epoxy resin material, the material composition and process conditions are optimized, and the problem of difficult to take into account both thermal conductivity and mechanical properties in the prior art is solved, and a high thermal conductivity and high strength epoxy resin material is achieved, which is suitable for the high-power operation state of semiconductor devices.
Patent Information
- Application Number
- CN202411894158.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-29
AI Technical Summary
When the prior art pursues high thermal conductivity, it usually sacrifices the mechanical properties of the material and increases the production cost, making it difficult to take into account both thermal conductivity and mechanical properties.
By adding a specific thermal filler and coupling agent to the epoxy resin material, the composition ratio and process conditions of the material are optimized to prepare a high thermal conductivity and high strength epoxy resin material.
It achieves a balance between high thermal conductivity and good mechanical properties of epoxy resin materials, which can meet the thermal conductivity requirements of semiconductor devices in high power operating states, and at the same time improves the overall performance of the material.
Smart Images

Figure BDA0005201297390000131 
Figure BDA0005201297390000141 
Figure BDA0005201297390000142
Abstract
Description
Technical Field
[0001] The present invention relates to the field of epoxy resin materials, and in particular to a high-thermal-conductivity, high-strength epoxy resin material and a preparation method and application thereof. Background Art
[0002] With the rapid development of 5G technology, the application scenarios and environments of electronic products have become more diversified. The operating power of some chips is getting higher and higher, and the heat generated is also increasing. This requires that the packaging material not only has certain mechanical properties to prevent the semiconductor chip from being damaged by the external environment, but also has good thermal conductivity. So that the heat generated during the operation of the chip can be transferred to the surface of the product in time, thereby maintaining a relatively stable temperature environment inside the chip, which is of great help in extending the service life of the chip.
[0003] Patent application CN105440588B discloses a high thermal conductivity moldable epoxy bottom filler and a preparation method thereof. By adding spherical thermal conductive fillers, the composition can obtain a composition with a thermal conductivity coefficient of up to 3.3 W / m·K.
[0004] Patent application CN111073217A discloses a high thermal conductivity and low stress epoxy molding compound for semiconductor packaging. The epoxy molding compound has a thermal conductivity of 3.5 W / m·K prepared by adjusting the proportion of thermal conductive fillers.
[0005] At present, most of the research has added a large amount of high thermal conductivity fillers in pursuit of high thermal conductivity. Although the thermal conductivity of the material has been greatly improved, it will also sacrifice some of the mechanical properties of the material and increase the preparation cost. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem in the prior art that it is difficult to balance the thermal conductivity and mechanical properties of plastic packaging materials, and to provide a high thermal conductivity and high strength epoxy resin material and a preparation method and application thereof. The epoxy resin material contains a thermally conductive filler and a coupling agent of a specific composition, and thus has high thermal conductivity and high strength, which can meet the thermal conductivity requirements of semiconductor devices under high power operation.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a high thermal conductivity and high strength epoxy resin material, which contains 2-11 weight % of epoxy resin, 1-6 weight % of curing agent, 80-90 weight % of thermal conductive filler, 0.1-1 weight % of ion capture agent, 0.1-1 weight % of low stress modifier, 0.1-1 weight % of coupling agent, 0.1-1 weight % of accelerator, 0.1-2 weight % of release agent, 1-10 weight % of flame retardant and 0.1-1 weight % of colorant based on the total weight of the epoxy resin material;
[0008] Wherein, the thermally conductive filler is obtuse silicon dioxide and spherical aluminum oxide;
[0009] The coupling agent is a mercapto coupling agent and an aminosilane coupling agent.
[0010] Preferably, based on the total weight of the epoxy resin material, the epoxy resin material contains 3-10 wt % of epoxy resin, 2-5 wt % of curing agent, 83-90 wt % of thermal conductive filler, 0.1-0.5 wt % of ion capture agent, 0.3-0.6 wt % of low stress modifier, 0.2-0.8 wt % of coupling agent, 0.1-0.5 wt % of accelerator, 0.1-1 wt % of release agent, 1-5 wt % of flame retardant and 0.1-0.5 wt % of colorant.
[0011] Preferably, the weight ratio of the obtuse silicon dioxide to the spherical aluminum oxide is 1-15:1, preferably 3-12:1.
[0012] Preferably, the particle size D50 of the obtuse-angled silica is 25-30 μm.
[0013] Preferably, the particle size D50 of the spherical alumina is 20-30 μm.
[0014] Preferably, the weight ratio of the mercapto coupling agent to the aminosilane coupling agent is 1-5:1, preferably 1-3:1.
[0015] Preferably, the epoxy resin is o-cresol-formaldehyde epoxy resin and / or dicyclopentadiene epoxy resin.
[0016] Preferably, the curing agent is selected from at least one of linear phenolic resin, XYLOK phenolic resin and biphenyl phenolic resin.
[0017] Preferably, the ion capture agent is selected from at least one of an anion capture agent, a cation capture agent, an anion-cation composite ion capture agent and a hydrotalcite compound.
[0018] Preferably, the low stress modifier is selected from at least one of silicone-modified epoxy resin, silicone resin and triblock copolymer containing silicone component.
[0019] Preferably, the accelerator is selected from at least one of triphenylphosphine, diphenyltetramethylimidazole and undecylimidazole.
[0020] Preferably, the release agent is oxidized polyethylene wax and / or monoglyceride wax.
[0021] Preferably, the flame retardant is at least one selected from a phosphorus-based flame retardant, a nitrogen-based flame retardant, a phosphorus-nitrogen flame retardant and a metal hydroxide flame retardant.
[0022] Preferably, the colorant is carbon black.
[0023] The second aspect of the present invention provides a method for preparing the high thermal conductivity and high strength epoxy resin material mentioned above, the method comprising: melt-mixing epoxy resin, curing agent, thermal conductive filler, ion capture agent, low stress modifier, coupling agent, promoter, release agent, flame retardant and colorant, and then molding the obtained mixture.
[0024] Preferably, the melt-mixing conditions include: a temperature of 75-100° C., preferably 75-85° C.; and a time of 5-20 min, preferably 7-9 min.
[0025] A third aspect of the present invention provides an application of a high thermal conductivity, high strength epoxy resin material in a semiconductor chip packaging process.
[0026] The high thermal conductivity and high strength epoxy resin material of the present invention adopts a thermal conductive filler and a coupling agent with a specific composition, which improves the thermal conductivity of the epoxy resin material on the one hand, and strengthens the bonding strength between the thermal conductive filler and each organic component in the epoxy resin material on the other hand, thereby significantly improving the thermal conductivity and mechanical strength of the epoxy resin material. The high thermal conductivity and high strength epoxy resin material can be used as a packaging material in the field of semiconductor chip packaging, which can simultaneously ensure the mechanical strength and thermal conductivity of the packaged product, thereby improving the life of the semiconductor chip. DETAILED DESCRIPTION
[0027] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0028] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0029] Based on the total weight of the epoxy resin material, the high thermal conductivity and high strength epoxy resin material of the present invention contains 2-11 weight % of epoxy resin, 1-6 weight % of curing agent, 80-90 weight % of thermal conductive filler, 0.1-1 weight % of ion capture agent, 0.1-1 weight % of low stress modifier, 0.1-1 weight % of coupling agent, 0.1-1 weight % of accelerator, 0.1-2 weight % of release agent, 1-10 weight % of flame retardant and 0.1-1 weight % of colorant;
[0030] Wherein, the thermally conductive filler is obtuse silicon dioxide and spherical aluminum oxide;
[0031] The coupling agent is a mercapto coupling agent and an aminosilane coupling agent.
[0032] In a more preferred embodiment, based on the total weight of the epoxy resin material, the epoxy resin material contains 2-11% by weight of epoxy resin, 1-6% by weight of curing agent, 80-90% by weight of thermal conductive filler, 0.1-1% by weight of ion capture agent, 0.1-1% by weight of low stress modifier, 0.1-1% by weight of coupling agent, 0.1-1% by weight of accelerator, 0.1-2% by weight of release agent, 1-10% by weight of flame retardant and 0.1-1% by weight of colorant. In the present invention, when the content of each component of the epoxy resin material is within the above range (especially within the preferred range), the epoxy resin material has good mechanical properties while having high thermal conductivity.
[0033] In the method of the present invention, the weight ratio of the obtuse silica to the spherical alumina can be 1-15: 1, preferably 3-12: 1. In the method of the present invention, when the weight ratio of the obtuse silica to the spherical alumina is within the above range (especially within the preferred range), the epoxy resin material has better thermal conductivity.
[0034] In some embodiments, based on the total weight of the epoxy resin material, the content of the obtuse silica is 50-80% by weight, preferably 55-80% by weight, and more preferably 60-70% by weight; the content of the spherical alumina is 10-40% by weight, preferably 15-40% by weight, and more preferably 20-40% by weight. In these embodiments, when the proportions of the obtuse silica and the spherical alumina are within the above range (especially within the preferred range), the epoxy resin material has better thermal conductivity.
[0035] In the present invention, the particle size D50 of the obtuse silica can be 25-30 μm, preferably 26-29 μm; the particle size D50 of the spherical alumina can be 20-30 μm, preferably 20-25 μm. In the present invention, when the particle sizes D50 of the obtuse silica and the spherical alumina are within the above range (especially within the preferred range), the epoxy resin material has good mechanical properties while having high thermal conductivity.
[0036] In the method of the present invention, the weight ratio of the mercapto coupling agent to the aminosilane coupling agent can be 1-5: 1, preferably 1-3: 1. In the method of the present invention, when the weight ratio of the mercapto coupling agent to the aminosilane coupling agent is within the above range (especially within the preferred range), the epoxy resin material has high thermal conductivity and good mechanical properties.
[0037] In some embodiments, based on the total weight of the epoxy resin material, the content of the mercapto coupling agent is 0.05-0.5% by weight, preferably 0.1-0.5% by weight, and more preferably 0.2-0.4% by weight; the content of the aminosilane coupling agent is 0.05-0.3% by weight, preferably 0.1-0.3% by weight, and more preferably 0.1-0.2% by weight. In these embodiments, when the proportions of the mercapto coupling agent and the aminosilane coupling agent are within the above range (especially within the preferred range), the epoxy resin material has good mechanical properties while having high thermal conductivity.
[0038] In the present invention, the epoxy resin may be o-cresol type epoxy resin and / or dicyclopentadiene type epoxy resin. In the present invention, when the epoxy resin is of the above type, the epoxy resin material has high thermal conductivity and good mechanical properties.
[0039] In the present invention, the curing agent can be at least one of linear phenolic resin, XYLOK phenolic resin and biphenyl phenolic resin, preferably linear phenolic resin. In the present invention, when the epoxy resin is of the above type, the epoxy resin material has high thermal conductivity and good mechanical properties.
[0040] In the present invention, the ion capture agent can be at least one of an anion capture agent, a cation capture agent, an anion-cation composite ion capture agent and a hydrotalcite compound, preferably a hydrotalcite compound. In the present invention, when the ion capture agent is of the above type (especially the preferred type), the epoxy resin material has good mechanical properties while having high thermal conductivity.
[0041] In the present invention, the low stress modifier can be at least one of silicone-modified epoxy resin, silicone resin and triblock copolymer containing silicone component, preferably silicone-modified resin. In the present invention, when the low stress modifier is of the above type (especially the preferred type), the epoxy resin material has good mechanical properties while having high thermal conductivity.
[0042] In the present invention, the accelerator can be at least one of triphenylphosphine, diphenyltetramethylimidazole and undecylimidazole, preferably a combination of triphenylphosphine and diphenyltetramethylimidazole. In the present invention, when the accelerator is of the above type (especially the preferred type), the epoxy resin material has good mechanical properties while having high thermal conductivity.
[0043] In the present invention, the release agent may be oxidized polyethylene wax and / or monoglyceride wax.
[0044] In the present invention, the flame retardant may be at least one of a phosphorus flame retardant, a nitrogen flame retardant, a phosphorus-nitrogen flame retardant and a metal hydroxide flame retardant, preferably zinc borate. In the present invention, when the flame retardant is of the above type (especially the preferred type), the epoxy resin material is more environmentally friendly.
[0045] In the present invention, the colorant may be carbon black.
[0046] The high thermal conductivity and high strength epoxy resin material of the present invention can be prepared by conventional methods in the art. In a preferred embodiment, a method for preparing a high thermal conductivity and high strength epoxy resin material is used for preparation, the method comprising: melt-kneading epoxy resin, curing agent, thermal conductive filler, ion capture agent, low stress modifier, coupling agent, accelerator, release agent, flame retardant and colorant, and then molding the obtained mixture.
[0047] In the method of the present invention, the melt-mixing conditions may include: a temperature of 75-100°C, preferably 75-85°C; a time of 5-20 minutes, preferably 7-9 minutes. In the method of the present invention, when the melt-mixing conditions are within the above range (especially within the preferred range), the prepared epoxy resin material has high thermal conductivity and good mechanical properties.
[0048] In some embodiments, the process of preparing the epoxy resin material may include: based on the total weight of the epoxy resin material, 2-11 wt % of epoxy resin, 1-6 wt % of curing agent, 80-90 wt % of thermal conductive filler, 0.1-1 wt % of ion capture agent, 0.1-1 wt % of low stress modifier, 0.1-1 wt % of coupling agent, 0.1-1 wt % of accelerator, 0.1-2 wt % of release agent, 1-10 wt % of flame retardant and 0.1- 1 wt% of colorant is mixed evenly, wherein the particle size D50 of the obtuse silica can be 25-30 μm, the particle size D50 of the spherical alumina can be 20-30 μm, the weight ratio of the obtuse silica to the spherical alumina can be 1-15:1, and the weight ratio of the mercapto coupling agent to the aminosilane coupling agent can be 1-5:1; then the obtained mixture is placed in a double-roll mixer and melt-mixed at 75-100°C for 5-20 minutes. The melt-mixed material is removed from the double-roll mixer and naturally cooled and crushed to obtain the high thermal conductivity and high strength epoxy resin material of the present invention. When the preparation method is implemented according to this embodiment, the prepared epoxy resin material has good mechanical properties while having high thermal conductivity.
[0049] The high thermal conductivity and high strength epoxy resin material of the present invention can be used in the semiconductor chip packaging process. The epoxy resin material has high strength and thermal conductivity, and can meet the requirements of semiconductor chips for heat dissipation performance under high-power operation. At the same time, it has high physical and mechanical properties, meets the use requirements of semiconductor materials in various environments, and has high reliability.
[0050] The following examples further illustrate the high thermal conductivity and high strength epoxy resin material and its preparation method and application described in the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.
[0051] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0052] Example 1
[0053] Based on the total weight of the epoxy resin material, epoxy resin (6 wt % of o-cresol epoxy resin and 1 wt % of dicyclopentadiene epoxy resin), curing agent (3.7 wt % of linear phenolic resin), inorganic filler (79 wt % of obtuse silica powder with a particle size D50 of 27 μm and 7.05 wt % of spherical alumina powder with a particle size D50 of 25 μm), flame retardant (1.2 wt % of zinc borate), accelerator (0.07 wt % of triphenylphosphine and 0.133 wt % of diphenyltetramethylimidazole), ion capture agent (0.25 wt % of tetramethylbenzene imidazole), and the like are added. % hydrotalcite), coupling agent (0.3 wt % mercapto coupling agent and 0.1 wt % amino coupling agent), low stress modifier (0.6 wt % silicone), release agent (0.15 wt % oxidized polyethylene wax and 0.15 wt % monoglyceride wax) and colorant (0.3 wt % carbon black) are mixed evenly, and then the obtained mixture is placed in a double-roll mixer and melt-mixed at 80°C for 8 minutes; the melt-mixed material is removed from the double-roll mixer and naturally cooled and crushed to obtain the high thermal conductivity and high strength epoxy resin material of the present invention. When the epoxy resin material is used in the semiconductor chip packaging process, the epoxy resin material is formed into a cake material, that is, the epoxy resin molding material for semiconductor packaging material is obtained.
[0054] Example 2
[0055] Based on the total weight of the epoxy resin material, epoxy resin (6 wt% of o-cresol epoxy resin and 1 wt% of dicyclopentadiene epoxy resin), curing agent (3.7 wt% of linear phenolic resin), inorganic filler (73 wt% of obtuse silica powder with a particle size D50 of 25 μm and 13.05 wt% of spherical alumina powder with a particle size D50 of 20 μm), flame retardant (1.2 wt% of zinc borate), accelerator (0.07 wt% of triphenylphosphine and 0.133 wt% of diphenyltetramethylimidazole), ion capture agent (0.25 % hydrotalcite), coupling agent (0.2% by weight mercapto coupling agent and 0.2% by weight amino coupling agent), low stress modifier (0.6% by weight silicone), release agent (0.15% by weight oxidized polyethylene wax and 0.15% by weight monoglyceride wax) and colorant (0.3% by weight carbon black) are mixed evenly, and then the obtained mixture is placed in a double-roll mixer and melt-mixed at 90°C for 5 minutes; the melt-mixed material is removed from the double-roll mixer and naturally cooled and crushed to obtain the high thermal conductivity and high strength epoxy resin material of the present invention. When the epoxy resin material is used in the semiconductor chip packaging process, the epoxy resin material is formed into a cake material, that is, the epoxy resin molding material for semiconductor packaging material is obtained.
[0056] Example 3
[0057] Based on the total weight of the epoxy resin material, epoxy resin (6 wt % of o-cresol epoxy resin and 1 wt % of dicyclopentadiene epoxy resin), curing agent (3.7 wt % of linear phenolic resin), inorganic filler (73 wt % of obtuse silica powder with a particle size D50 of 30 μm and 13.05 wt % of spherical alumina powder with a particle size D50 of 30 μm), flame retardant (1.2 wt % of zinc borate), accelerator (0.07 wt % of triphenylphosphine and 0.133 wt % of diphenyltetramethylimidazole), ion capture agent (0.25 wt % of tetramethylbenzene imidazole), and the like are added. % hydrotalcite), coupling agent (0.3 wt % mercapto coupling agent and 0.1 wt % amino coupling agent), low stress modifier (0.6 wt % silicone), release agent (0.15 wt % oxidized polyethylene wax and 0.15 wt % monoglyceride wax) and colorant (0.3 wt % carbon black) are mixed evenly, and then the obtained mixture is placed in a double-roll mixer and melt-mixed at 75°C for 20 minutes; the melt-mixed material is removed from the double-roll mixer and naturally cooled and crushed to obtain the high thermal conductivity and high strength epoxy resin material of the present invention. When the epoxy resin material is used in the semiconductor chip packaging process, the epoxy resin material is formed into a cake material, that is, the epoxy resin molding material for semiconductor packaging material is obtained.
[0058] Example 4
[0059] Based on the total weight of the epoxy resin material, epoxy resin (4.8 wt % of o-cresol epoxy resin and 0.94 wt % of dicyclopentadiene epoxy resin), curing agent (3.56 wt % of linear phenolic resin), inorganic filler (67.1 wt % of obtuse silica powder with a particle size D50 of 27 μm and 20.44 wt % of spherical alumina powder with a particle size D50 of 25 μm), flame retardant (1.17 wt % of zinc borate), accelerator (0.07 wt % of triphenylphosphine and 0.133 wt % of diphenyltetramethylimidazole), ion capture agent (0 .24 wt% hydrotalcite), coupling agent (0.2 wt% mercapto coupling agent and 0.2 wt% amino coupling agent), low stress modifier (0.58 wt% silicone), release agent (0.15 wt% oxidized polyethylene wax and 0.15 wt% monoglyceride wax) and colorant (0.29 wt% carbon black) are mixed evenly, and then the obtained mixture is placed in a double-roll mixer and melt-mixed at 80°C for 8 minutes; the melt-mixed material is removed from the double-roll mixer and naturally cooled and crushed to obtain the high thermal conductivity and high strength epoxy resin material of the present invention. When the epoxy resin material is used in the semiconductor chip packaging process, the epoxy resin material is formed into a cake material, that is, the epoxy resin molding material for semiconductor packaging material is obtained.
[0060] Example 5
[0061] Based on the total weight of the epoxy resin material, epoxy resin (4.23 wt % of o-cresol epoxy resin and 0.71 wt % of dicyclopentadiene epoxy resin), curing agent (2.61 wt % of linear phenolic resin), inorganic filler (67.61 wt % of obtuse silica powder with a particle size D50 of 27 μm and 22.43 wt % of spherical alumina powder with a particle size D50 of 25 μm), flame retardant (0.85 wt % of zinc borate), accelerator (0.05 wt % of triphenylphosphine and 0.09 wt % of diphenyltetramethylimidazole), ion capture agent ( 0.18 wt% hydrotalcite), coupling agent (0.3 wt% mercapto coupling agent and 0.1 wt% amino coupling agent), low stress modifier (0.42 wt% silicone), release agent (0.11 wt% oxidized polyethylene wax and 0.11 wt% monoglyceride wax) and colorant (0.21 wt% carbon black) are mixed evenly, and then the obtained mixture is placed in a double-roll mixer, melt-mixed at 80°C for 8 minutes, and the melt-mixed material is removed from the double-roll mixer and naturally cooled and crushed to obtain the high thermal conductivity and high strength epoxy resin material of the present invention. When the epoxy resin material is used in the semiconductor chip packaging process, the epoxy resin material is formed into a cake material, that is, the epoxy resin molding material for semiconductor packaging material is obtained.
[0062] Example 6
[0063] This embodiment is implemented according to the method described in Embodiment 1, except that, based on the total weight of the epoxy resin material, the inorganic filler contains 81.75 weight % of obtuse silica powder with a particle size D50 of 27 μm and 4.3 weight % of spherical alumina powder with a particle size D50 of 25 μm, and the weight ratio of the obtuse silica powder to the spherical alumina powder is 19:1.
[0064] Example 7
[0065] This embodiment is implemented according to the method described in Embodiment 1, except that, based on the total weight of the epoxy resin material, the inorganic filler contains 23 weight % of obtuse silica powder with a particle size D50 of 5 μm and 63.05 weight % of spherical alumina powder with a particle size D50 of 50 μm, and the weight ratio of the obtuse silica powder to the spherical alumina powder is 0.36:1.
[0066] Example 8
[0067] This embodiment is implemented according to the method described in Embodiment 1, except that, based on the total weight of the epoxy resin material, the coupling agent contains 0.36 wt % of a thiol coupling agent and 0.04 wt % of an amino coupling agent, and the weight ratio of the thiol coupling agent to the amino coupling agent is 9:1.
[0068] Comparative Example 1
[0069] This comparative example was implemented according to the method described in Example 1, except that, based on the total weight of the epoxy resin material, the inorganic filler contained 86.05 wt % of obtuse silica powder with a particle size D50 of 27 μm.
[0070] Comparative Example 2
[0071] This comparative example was implemented according to the method described in Example 1, except that, based on the total weight of the epoxy resin material, the inorganic filler contained 86.05 wt % of spherical alumina powder with a particle size D50 of 25 μm.
[0072] Comparative Example 3
[0073] This comparative example is implemented according to the method described in Example 1, except that, based on the total weight of the epoxy resin material, the coupling agent contains 0.4 wt % of a mercapto coupling agent.
[0074] Comparative Example 4
[0075] This comparative example is implemented according to the method described in Example 1, except that, based on the total weight of the epoxy resin material, the coupling agent contains 0.4 wt % of an amino coupling agent.
[0076] Test Case
[0077] This test example is used to illustrate the gel time, fluidity, water absorption, flame retardancy, thermal conductivity, glass transition temperature (Tg), thermal expansion coefficient (CTE1 / CTE2) and mechanical properties of the epoxy resin materials prepared in Examples 1-8 and Comparative Examples 1-4. The specific test steps are as follows:
[0078] Gelation time: Heat the electric hot plate to 175±1℃, take 2-3g of sample and place it on the iron plate, stir it continuously with a small needle, and test the time it takes for the sample to change from fluid to gel.
[0079] Fluidity: Take 30g of sample and measure it with a resin transfer injection molding machine using a spiral flow metal mold. The injection pressure is 70kgf / cm 2 , the mold temperature is 175±1℃.
[0080] Water absorption rate: The water absorption rate test is carried out according to the "PCT24" method, where the sample size is 50mm*3mm (diameter*thickness), and the test conditions are 121°C, 100RH%, 2atm, and 24h; the water absorption rate is calculated as follows: the weight increase of the sample after PCT24 / the initial weight of the sample*100%.
[0081] Flame retardancy: vertical combustion method is adopted according to GB / T 2408 standard.
[0082] Thermal conductivity: Steady state method is used according to GB / T 10294 standard.
[0083] Glass transition temperature (Tg), storage modulus: The Tg of EMC in the present invention can be determined by dynamic mechanical analysis (DMA) or thermomechanical analysis (TMA), and the storage modulus is determined by DMA. First, the EMC powder is cured for 150 seconds at a mold temperature of 180°C in a molding machine to make a sample bar / sheet, and then placed in an oven at 180°C for post-curing for 6 hours. The size of the sample block for TMA testing is 5mm*5mm (diameter*thickness); the size of the sample bar for DMA testing is 60mm*13mm*3.2mm (length*width*thickness).
[0084] Thermal expansion coefficient (CTE1 / CTE2): measured using the above-mentioned TMA.
[0085] Mechanical properties: For specific steps and operating methods, refer to the industry standard GB / T 9341-2008.
[0086] The results are shown in Table 1.
[0087] Table 1
[0088]
[0089]
[0090] Table 1
[0091]
[0092] It can be seen from the results in Table 1 that, compared with Comparative Examples 1-4, the epoxy resin material of the present invention prepared in Examples 1-8 has a higher thermal conductivity, which is maintained at 2.2-3.0 W / m·k, and has good mechanical properties. The mold opening strength is ≥32 MPa, and the mold opening modulus is ≥491 MPa, which can meet the thermal conductivity requirements of semiconductor devices under high-power operation. In the unpreferred embodiment 6, due to the high content of obtuse silica powder added during the preparation process, the strength of the prepared epoxy resin material is higher, but the fluidity and thermal conductivity are sacrificed; in the unpreferred embodiment 7, due to the high content of spherical alumina powder added during the preparation process, the thermal conductivity and fluidity of the prepared epoxy resin material are better, but the mechanical properties are sacrificed; in the unpreferred embodiment 8, due to the high ratio of the mercapto coupling agent to the amino coupling agent added during the preparation process, its copper adhesion is lower than that of the preferred embodiments 1-6. In Comparative Example 1, since only obtuse silica powder was added, its mechanical properties were further increased, while the thermal conductivity was lower than 2.2 W / m·k; in Comparative Example 2, since only spherical alumina powder was added, its thermal conductivity was further increased, while the mold opening strength was only 30 MPa, and the mold opening modulus was only 426 MPa; in Comparative Examples 3 and 4, since only one coupling agent was added, its copper adhesion was only 103 N and 158 N, which was difficult to meet industrial applications.
[0093] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A high thermal conductivity and high strength epoxy resin material, characterized in that: Based on the total weight of the epoxy resin material, the epoxy resin material contains 2-11 wt % of epoxy resin, 1-6 wt % of curing agent, 80-90 wt % of thermal conductive filler, 0.1-1 wt % of ion capture agent, 0.1-1 wt % of low stress modifier, 0.1-1 wt % of coupling agent, 0.1-1 wt % of accelerator, 0.1-2 wt % of release agent, 1-10 wt % of flame retardant and 0.1-1 wt % of colorant; Wherein, the thermally conductive filler is obtuse silicon dioxide and spherical aluminum oxide; The coupling agent is a mercapto coupling agent and an aminosilane coupling agent.
2. The epoxy resin material according to claim 1, characterized in that: Based on the total weight of the epoxy resin material, the epoxy resin material contains 3-10 weight % of epoxy resin, 2-5 weight % of curing agent, 83-90 weight % of thermal conductive filler, 0.1-0.5 weight % of ion capture agent, 0.3-0.6 weight % of low stress modifier, 0.2-0.8 weight % of coupling agent, 0.1-0.5 weight % of accelerator, 0.1-1 weight % of release agent, 1-5 weight % of flame retardant and 0.1-0.5 weight % of colorant.
3. The epoxy resin material according to claim 1 or 2, characterized in that: The weight ratio of the obtuse-angled silicon dioxide to the spherical aluminum oxide is 1-15:1, preferably 3-12:
1.
4. The epoxy resin material according to any one of claims 1 to 3, characterized in that: The particle size D50 of the obtuse-angled silica is 25-30 μm.
5. The epoxy resin material according to any one of claims 1 to 3, characterized in that: The particle size D50 of the spherical alumina is 20-30 μm.
6. The epoxy resin material according to claim 1 or 2, characterized in that: The weight ratio of the mercapto coupling agent to the aminosilane coupling agent is 1-5:1, preferably 1-3:
1.
7. The epoxy resin material according to claim 1 or 2, characterized in that: The epoxy resin is o-cresol type epoxy resin and / or dicyclopentadiene type epoxy resin; and / or The curing agent is selected from at least one of linear phenolic resin, XYLOK phenolic resin and biphenyl phenolic resin; and / or The ion capture agent is selected from at least one of an anion capture agent, a cation capture agent, an anion-cation composite ion capture agent and a hydrotalcite compound; and / or The low stress modifier is selected from at least one of silicone-modified epoxy resin, silicone resin and triblock copolymer containing silicone component; and / or The accelerator is selected from at least one of triphenylphosphine, diphenyltetramethylimidazole and undecylimidazole; and / or The release agent is oxidized polyethylene wax and / or monoglyceride wax; and / or The flame retardant is selected from at least one of a phosphorus flame retardant, a nitrogen flame retardant, a phosphorus-nitrogen flame retardant and a metal hydroxide flame retardant; and / or The colorant is carbon black.
8. A method for preparing the high thermal conductivity and high strength epoxy resin material according to any one of claims 1 to 7, characterized in that: The method comprises: melting and mixing epoxy resin, curing agent, thermal conductive filler, ion capture agent, low stress modifier, coupling agent, accelerator, mold release agent, flame retardant and colorant, and then molding the obtained mixture.
9. The preparation method according to claim 8, characterized in that: The melt mixing conditions include: temperature of 75-100° C., preferably 75-85° C.; time of 5-20 min, preferably 7-9 min.
10. Use of the high thermal conductivity and high strength epoxy resin material according to any one of claims 1 to 7 in a semiconductor chip packaging process.
Citation Information
Patent Citations
A high thermal conductivity molding epoxy underfiller, its preparation method and applications
CN105440588B
High-thermal-conductivity and low-stress epoxy molding compound for semiconductor packaging
CN111073217A